At the tavern with Taylor Swift: a gothic and/or dark romantic reading of the album ‘The tortured poets Department" - Claudio Fernandes Baranhuke Júnior (Babel)
This essay was inspired by a pedagogical dilemma I encountered in North American literature classes I conducted at a public university in Paraná State, Brazil. According to Menezes (2015), there are many challenges to teaching English language literature in English to non-Anglophone speakers. During my lessons on Dark Romantic literature, I realized that that content was arduous for the students, so I sought to make the subject more engaging. Integrating music into the curriculum emerged as a potential solution (Lira, 2018). Therefore, this study offers a gothic and/or dark romantic reading of Taylor Swift’s album The Tortured Poets Department.